Penggunaan Accelerometer MMA7361 sebagai Alternatif Pengukuran Lendutan pada Jembatan Secara Nirkabel Berbasis ATmega32 - Mohd Syaryadhi; Purwandy Hasibuan; Suhardi Suhardi (Jurnal Rekayasa Elektrika, 2015)
A bridge is planned and built with a certain capability against vehicles through it. The vehicles movement causes vibration and vertical deflection on certain parts of the bridge. If the vibration occurs continuously in a great value, then the bridge will be damaged sooner than had been planned. This research reports a design of a vertical deflection measuring system prototype on bridge, employing an accelerometer MMA7361 sensor which is controlledby ATmega32. The system was tested by manually loading the trial bridge with 1 m of length. The loading deflects down the bridge to maximum 15 cm from the reference point. Sensor readout data was sent wirelessly using ZigBee real time to computer in a graphical display for easy analysis. The research give an alternative method in vertical deflection measuring on the bridge that can be utilized by stakeholder in policy decision.